A study of awareness of generic drugs amongst residents and intern doctors in a tertiary care hospital in Surat city - Patel, Krima H.; Banzal, Neeta; Hingorani, Sadhana K.; Desai, Anupama (International Journal of Basic & Clinical Pharmacology, 2025)
Background: As defined by WHO generic drug is “a pharmaceutical product which is intended to be interchangeable with an innovator product that is manufactured without a license from the innovator company and marketed after the expiry date of the patent or other exclusive rights”. They are made with the same active substance as the non-generic drugs which are already authorized and approved for their safety, efficacy and quality before getting licensed. Methods: A cross-sectional, prospective, questionnaire-based study was conducted on 115 residents and intern doctors. Awareness and knowledge about generic drugs were checked using pre-validated questionnaire which was followed by an educational intervention and post-questionnaire. The collected data was analysed using MS-excel. Results: The 94 participants voluntarily responded. As per the result of pre-test many participants were not aware of the difference between generic and branded drug, but after conducting educational intervention, increase in knowledge about generic drugs, branded drugs, safety, efficacy, availability and regulation regarding prescription of generic drug was seen. In post-test, 98.94% believed that generic drugs are cheaper than branded drugs and 95.74% agreed that generic drugs are as safe as branded drugs, while 97.87% believed increasing awareness regarding generic drugs will increase acceptability of generic drugs. Conclusions: The reasons for opting branded drugs were lack of awareness regarding efficacy, safety, acceptability and availability of generic drugs. Periodic training program would help in clearing doubts, enhance the prescribing of generic drugs and reduce the health expenditure and economic burden.